ASPECTS OF TEACHING FOREIGN LANGUAGES AT A TECHNICAL UNIVERSITY - M.B, Ganihanova (International Journal of Psychosocial Rehabilitation, 2020)
Media education, as a set of means and methods of teaching youth today is more relevant than ever. Changes in education occurring under the influence of the rapid introduction of information technology in all spheres of life, impose serious requirements on the level of competence of a teacher who needs to master the role of a consultant for a student. Researchers and educators from around the world emphasize the special need for media education. It is assumed that a media literate teacher will be able to:• encourage and develop students' desire to ask well-founded problematic questions related to the media;• use a research methodology in teaching, when students can independently search for (media) information to answer various questions, apply the knowledge gained in the training course to new areas.• help pupils / students to develop the ability to use a variety of primary sources (media) of information to explore problems and then draw general conclusions;• organize discussions, where students learn to listen to others tolerantly and tactfully express their own opinions, including about media texts;• support open discussions where there are no definitive answers to many questions;• encourage students to reflect on their own media experiences and act on the basis of